A case report of Traumatic Asphyxia - Sah, B; Yadav, BN; Jha, S (Journal of College of Medical Sciences-Nepal, 2015)
Traumatic asphyxia is a condition presenting with cervicofacial cyanosis and edema, subconjunctival hemorrhage, and petechial hemorrhages of the face, neck, and upper chest that occurs due to a compressive force to the thoracoabdominal region. In this case report a 52 years old lady who was brought to the mortuary because of death due to traumatic asphyxia as a result of being stampeded by her own cows upon her chest was discussed. Congestion on both the conjunctiva, cyanosis on chin and adjacent upper left side of neck found with a well demarcated area observed between the cyanosed area over face and the normal area of neck. Hematoma was present in the chin and the adjacent neck region. Apart from quickly eliminating organ pathologies and initiation of supportive therapy in a case of traumatic asphyxia, possibility of formation of hematoma in neck after few hours of getting injured should also be considered, as this type of hematoma may contribute to the cause of death. Journal of College of Medical Sciences-Nepal, 2014, Vol-10, No-3, 51-55